Potensi Zakat Hasil Perkebunan Kelapa Sawit di Desa Suka Maju Kecamatan Mandiangin Timur Kabupaten Sarolangun - Indah Damayanti; Maulana Yusuf; Ogi Saputra (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
Crop and fruit crops are one type of zakat that must be paid. In the implementation of zakat for oil palm farmers in Suka Maju Village, East Mandiangin District, Sarolangun Regency, there are already some oil palm farmers who pay zakat for oil palm. However, some oil palm farmers do not understand agricultural zakat so they do not carry out their zakat obligations and they also think that the income they receive is small. The aim of this research is to describe the implementation of zakat from oil palm plantations and analyze the potential for zakat from oil palm plantations in Suka Maju Village, East Mandiangin District, Sarolangun Regency. The type of research used in this research is qualitative research. Data collection techniques using observation, interviews and documentation. The analytical method used was Miles and Huberman's theory, namely Data Collection, Data Reduction, Data Presentation, and Conclusion and Verification. The results of the research concluded that: (1) The implementation of zakat on oil palm plantations in Suka Maju Village shows diversity in the application of the conditions, calculations and amounts of zakat issued by farmers where in its implementation, the amount of zakat issued does not show conformity with these calculations; (2) The potential for zakat from oil palm plantations in Suka Maju Village, East Mandiangin District, Sarolangun Regency based on calculations on 43,000 Kg of harvest on 43 Ha of land with a natural irrigation system is IDR. 6,950,000/month.